A systematic review of early childhood research on socioemotional development and prosocial behaviour - Isha, Siti Rahayu; Azam, Naqi Dahamat; Daud, Mohd Najmi; Ismail, Hazhari (Human Resource Management Academic Research Society, 2023)
Understanding the relationship between prosocial behaviour, emotional intelligence, and parent-child attachment is crucial for future research into maintaining positive social relationships and promoting social adjustment, particularly in young children. Therefore, this systematic review critically explores the gaps in the relationship between parent-child attachment, emotional intelligence and prosocial behaviour. According to the findings, there are few gaps in the relationship between parent-child attachment, emotional intelligence and prosocial behaviour. By analysing 12 selected articles, the current study identifies and categorises gaps in four themes: influencing factors, populations and sampling, methodology, and outcomes. This systematic review highlights gaps in research, including insufficient focus on multiple mediators and moderators, small sample sizes, specific population contexts, reliance on cross-sectional designs, and overlooking longitudinal perspectives. This systematic review highlights critical areas of parent-child attachment, emotional intelligence, and prosocial behaviour. Addressing these gaps is essential to improve understanding of this complex relationship and to guide future research.